ACE1 transcription factor produced in Escherichia coli binds multiple regions within yeast metallothionein upstream activation sequences. - Evans, C F (1990)
The ACE1 protein of Saccharomyces cerevisiae was expressed as a trpE-ACE1 fusion protein in Escherichia coli and shown to bind CUP1 upstream activation sequences at multiple regions in a copper-inducible manner. These binding sites contain within them the sequence 5'-TC(T)4-6GCTG-3', which we propose constitutes an important part of the ACE1 consensus recognition sequence.